Faktor Dominan yang Mempengaruhi Tingginya Kasus TB Paru - I Ketut Sudiantara; I Dewa Putu Gede Putra Yasa; Sitti Fatmawati (Jurnal Gema Keperawatan, 2015)
The purpose of this research was to identified Dominant factor that influence of height incident of lung Tuberculosis. Design of study is descriptive design with cross sectional approach. Study was loceted at public health center I of Sukawati on Jun 2014. Lung Tuberculosis patients who have look at the public health center I of Sukawati as sample. Number of sampel was 34 lung tuberculosis patinents, was taken by using purposive sampling. Influence factor as data primier was collected by using questioner. Result of study was showed the dominant factor is predisposing factor 18 respondents (53%). From the result showed height risk for spereted lung tuberculosis infection